Suppression of Postprandial Glycaemia by L-Arabinose in Rats is More Associated with Starch than Sucrose Ingestion - Short Report - Jurgoński Adam; Krotkiewski Marcin; Juśkiewicz Jerzy; Billing-Marczak Katarzyna (Polish Journal of Food and Nutrition Sciences)
The aim of this study was to verify the glycaemia-lowering activity of L-arabinose. The experiment was conducted on 3 individual days, each separated by a week. At the beginning of each week rats were subjected to an oral glucose, sucrose or starch tolerance test. Five minutes prior to each test rats were gavaged with water (a control), an aqueous solution of acarbose (a positive control) and L-arabinose. There was no effect of L-arabinose on glycaemia in the glucose tolerance test, whereas it reduced postprandial glycaemia after 15 min of the sucrose tolerance test. In the starch tolerance test, the glycaemia after L-arabinose ingestion was significantly decreased both at time intervals and in total. Inhibition of enzyme activity involved in starch digestion (amylase, maltase) may be suggested as the most probable mechanism responsible for the observed effects